Struktur Sosial dan Dinamika Persekutuan Hukum Adat di Indonesia: Kajian terhadap Kekerabatan, Ketetanggaan, dan Keorganisasian - Lubabin Nawval Muhammad; Najwa Faridillah; Akbar, Mohammad Hikmal (Taruna Law: Journal of Law and Syariah, 2025)
This study comprehensively reviews the structure and dynamics of customary law communities in Indonesia, which until now still play a vital role in the social order of traditional communities. This material highlights three main forms of customary law associations, namely: kinship associations, neighborhood associations, and organizational associations, each with its own characteristics, structures, and governance systems. The close relationship between individuals and customary communities is also reviewed, where personal interests are always weighed against communal and social values. This study also explores how customary law is not only a legal instrument, but also part of the cultural identity of local communities that regulate the rights and obligations of its citizens collectively. In addition, it also highlights the challenges faced by customary law in dealing with external influences such as colonization, modernization, globalization, and changes in national law, which have the potential to erode local wisdom values. This material provides an overview of the importance of preserving and revitalizing customary law as part of the nation's rich and diverse cultural heritage. With a multidisciplinary approach, this discussion is not only descriptive but also reflective, making this paper relevant to legal studies, anthropology, and public policy based on local wisdom.